The three subtypes of tick-borne encephalitis virus induce encephalitis in a natural host, the bank vole (Myodes glareolus). - Elina Tonteri (Public Library of Science (PLoS), 2013)
Tick-borne encephalitis virus (TBEV) infects bank voles (Myodes glareolus) in nature, but the relevance of rodents for TBEV transmission and maintenance is unclear. We infected colonized bank voles subcutaneously to study and compare the infection kinetics, acute infection, and potential viral persistence of the three known TBEV subtypes: European (TBEV-Eur), Siberian (TBEV-Sib) and Far Eastern (TBEV-FE). All strains representing the three subtypes were infective and highly neurotropic. They induced (meningo)encephalitis in some of the animals, however most of the cases did not present with apparent clinical symptoms. TBEV-RNA was cleared significantly slower from the brain as compared to other organs studied. Supporting our earlier findings in natural rodent populations, TBEV-RNA could be detected in the brain for up to 168 days post infection, but we could not demonstrate infectivity by cell culture isolation. Throughout all time points post infection, RNA of the TBEV-FE was detected significantly more often than RNA of the other two strains in all organs studied. TBEV-FE also induced prolonged viremia, indicating distinctive kinetics in rodents in comparison to the other two subtypes. This study shows that bank voles can develop a neuroinvasive TBEV infection with persistence of viral RNA in brain, and mount an anti-TBEV IgG response. The findings also provide further evidence that bank voles can serve as sentinels for TBEV endemicity.